IMPACT OF SOCIAL MEDIA USE ON COMMUNITY PSYCHOLOGY AND ITS IMPLICATIONS IN COUNSELING - Silvianetri Silvianetri (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2021)
Social media is a communication tool that is commonly used by everyone in today's technological era. Excessive use of social media will cause addiction, and have an impact on people's psychology. This article aims to reveal data on the impact of social media addiction on the psychology of society and its implications for counseling. The research uses qualitative research methods, especially phenomenology. The research instrument is the researcher himself, and for data collection using in-depth interviews and observation. The research respondents are the people of West Sumatra with male and female sexes aged 15 to 50 years. The data analysis technique is using Miles and Huberman data analysis with the following steps; data reduction, data display, and conclusion drawing/verification. The results of the study found that the psychological impact of social media addiction generally affects people's cognitive and emotions. The positive impact is cognitive, namely increasing insight and thinking skills, as well as giving birth to various creative ideas. The negative impact is causing forgetfulness, panic, dead-end thoughts, lack of logical thinking. Emotionally the positive impact of using social media by the community is to create happiness, optimism, motivation, enthusiasm, enthusiasm. The negative impact is causing anxiety, despair, sadness, resentment, anger and frustration. The results of this study have implications for counseling, namely preventively developing counseling techniques that aim to reduce social media addiction. Curatively, it can develop counseling techniques that can improve brain function and reduce anxiety levels.